Factors Influencing Intention to Use Blockchain Technology among Textile Manufacturing Sectors in Johor - Sim, Hong Liang; Kamaruddin, Kamariah (Research in Management of Technology and Business, 2023)
Manufacturing sectors have become increasingly complicated, with numerous layers of suppliers located all over the world. As a result, visibility and traceability are difficult to achieve as items move through the supply chain. Blockchain technology have the ability to simplify supply chain operations and increase transparency in business and industrial processes. It has the ability to advance various facets of the industrial sector and make it quicker, more dependable, and more affordable. In this study, the researcher aims to identify the level of intention to use blockchain technology among textile manufacturing sectors and to determine the relationship between attitude, perceived behavior control, subjective norms and intention to use blockchain technology among textile manufacturing sectors in Johor, utilizing the Theory of Planned Behavior (TPB). Quantitative approaches focus on this study and the sample collect based on the sample who answer the questionnaires. The response rate was 70.27% which was 104 out of 148 and all of the questionnaires collected were usable. Data have been analyzed using SPSS statistical software. The results of Spearman’s Correlation Coefficient, r is 0.604 which was a strong relationship between attitude and intention to use blockchain technology. Therefore, H1 is supported. Next, r is 0.547 which was a moderate relationship between perceived behavioral control and intention to use blockchain technology. Therefore, H2 is supported. There is a very strong relationship between subjective norms and intention to use blockchain technology where the r is 0.827. Therefore, H3 is supported. This finding may be a reference for textile manufacturing sectors know factors that influencing the level of intention to use blockchain technology.